Preparedness of Healthcare Workers towards Handling COVID-19 Outbreak in the Gambia - Joseph W Jatta; Jean Claude Romaric Pingdwindé Ouédraogo; Yusupha Sanyang; Daniel Nebongo; Tahir Ahmed Touray; Dodou Sanyang (Ital Publication, 2021)
Background: The novel Coronavirus (COVID-19) outbreak that began in Wuhan, China rapidly became a public health concern and a challenge for healthcare systems globally.  In the wake of the first confirmed case in The Gambia, concerns were raised in some quarters about the health system's preparedness to handle the outbreak. Therefore, we aimed to assess health personnel's knowledge and preparedness in fighting the COVID-19 outbreak in The Gambia. Methods: A cross-sectional survey was conducted using self-administered questionnaires distributed online through social media. Descriptive, bivariate, and binary logistic analyses were done using SPSS Version 22. Results: We obtained 333 valid responses. Most participants reported that their health facility has some form of preparedness; however, only a small proportion reported enough PPEs in the health facility. About half (50.5%) showed good knowledge of COVID-19. There was a statistically significant difference among the professions regarding their reaction if they were found positive of COVID-19 (p=0.006). There was a significant association between health professions [other professions (Odds ratio [OR]=0.2, 95% Confidence interval [CI]:0.04-0 .9; p=0.038)] and overall knowledge of COVID-19. Conclusion: Our findings showed some form of preparedness towards COVID-19 among healthcare workers. However, many aspects, such as the availability of PPEs and their proper use and knowledge, need improvement. Thus, training and an adequate supply of equipment are required to better respond to upcoming COVID-19 waves and future outbreaks.   Doi: 10.28991/SciMedJ-2021-03-SI-5 Full Text: PDF